EFEKTIFITAS FRAKSI SAPONIN BIJI KLABET (Trigonella foenum graecum L.) TERHADAP KADAR HORMON TESTOSTERON TIKUS JANTAN SPRAGUE DAWLEY®. - Yusneli .; Nyayu Fauziah Zen; Hamril Dani (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2021)
Saponins are active compounds contained in the seeds of klabet, which may inhibit the development of spermatogenic cells through hormonal effects. The aim of this study was to determine the effectiveness of giving klabet seed saponins (Trigonella foenum-graecum L.) on testosterone levels in male Sprague Dawley® rats. The study was a laboratory experimental study, the number of samples was 24 male rats and the saponin material of klabet seeds with a dose per 300gr BW of 40mg, 80mg and 120mg, and control, treatment for 24 days. The study through the Anova test on all variables showed a significant decrease with a value of p = 0.000 followed by the Post Hoc test which resulted in a significant decrease in testosterone levels in all groups. From the results, it can be concluded that the saponin fraction of klabet seeds can reduce testosterone levels.